Pengaruh Laba Akuntansi, Total Arus Kas Dan Size Perusahaan Terhadap Return Saham Pada Perusahaan Manufaktur Sektor Aneka Industri Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode Tahun 2013-2017 - HERDIAN, CHINTYA NINDYA; Mintarti, Sri; Pattisahusiwa, Salmah (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
This study aims to examine the effect of accounting earnings, total cash flow, company size on stock returns using a multiple regression approach. This study uses a purposive sampling data method that is data from 2013-2017 in the financial statements or annual reports of various industrial companies obtained on the Indonesia Stock Exchange (IDX). The study population was 43 manufacturing companies listed on the Indonesia Stock Exchange (IDX). The procedure in selecting samples uses a purposive sampling method and produces 14 various industry companies that meet the sample selection criteria. Research data is collected from the annual report for the 2013-2017 period. Based on the purposive sampling method, there are 70 samples. The data analysis method used is descriptive statistical analysis, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, f test, coefficient of determination, multiple regression analysis, and t test. The results of hypothesis testing show that the independent variables of accounting earnings have a significant positive effect and the total cash flow has a significant positive effect on stock returns. While the independent variable size of the company has a negative and insignificant effect.